Pengelolaan Sumberdaya Arkeologi di Situs Pekauman - Trias Anditasari, Nur; Srijaya, Wayan; Agung Bawono, Rochtri (Humanis; Vol 26 No 4 (2022), 2022)
Pekauman is a village that has a heritage of archeological resources. Relics found in the form of relics in the era before knowing writing. The purpose of this study is to explain the management of archaeological resources in Pekauman Village as a cultural tourism object in Bondowoso Regency. This study uses a descriptive qualitative method that goes through the stages of collecting data from literature, observation, interviews and analyzed using qualitative analysis, contextual analysis, and SWOT analysis. The results of this study obtained an overview of the damage and consequences of damage to cultural heritage objects in the form of human, natural, and weather factors. Cultural heritage objects studied include menhirs, kenong stones, sarcophagi, and dolmens. Stages of treatment by cleaning the object's environment, cleaning mildew and other treatments.